Linguistic Aspect of Advertising - Kolomiiets, Alina; Yakymenko, Olena (My University, 2016)
The article deals with the linguistic aspect of advertising. The aim of this article is to show the process of manipulating human’s emotions via advertisements and to show different linguistic techniques and tricks that advertisers use to attract consumer’s attention.
Keywords: кафедра іноземних мов професійного спрямування; advertising; manipulation; emotion; consumer; linguistic techniques; реклама; маніпуляція; емоція; споживач; лінгвістичні техніки; манипуляция; эмоция; потребитель; лингвистические техники